2003
DOI: 10.1093/jn/133.1.160
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Lipids, Vitamin D Metabolites, Retinol, Retinyl Esters, Tocopherols and Selected Carotenoids in Twelve Captive Wild Felid Species at Four Zoos

Abstract: Serum concentrations of several nutrients were measured in 12 captive wild felid species including caracal (Felis caracal), cheetah (Acinonyx jubatus), cougar (Felis concolor), fishing cat (Felis viverrinus), leopard (Panthera pardus), lion (Panthera leo), ocelot (Felis pardalis), pallas cat (Felis manul), sand cat (Felis margarita), serval (Felis serval), snow leopard (Panthera uncia) and tiger (Panthera tigris). Diet information was collected for these animals from each participating zoo (Brookfield Zoo, For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…In domestic cats, a study found 70 ± 17% of total plasma VA by weight was esterified, and of this, 61 ± 6% was retinyl stearate, 36 ± 13% was retinyl palmitate, and 5 ± 3% was retinyl oleate [18]. In a study surveying serum retinoids in 12 captive wild felid species, retinyl esters, predominantly stearate and palmitate, were detected in the serum of all species measured [27]. However, the proportion of VA present as esters ranged widely from 87% in the sand cat and 48% in the fishing cat to as low as 7% in cheetahs and cougars and 4% in servals.…”
Section: Vitamin Amentioning
confidence: 99%
See 1 more Smart Citation
“…In domestic cats, a study found 70 ± 17% of total plasma VA by weight was esterified, and of this, 61 ± 6% was retinyl stearate, 36 ± 13% was retinyl palmitate, and 5 ± 3% was retinyl oleate [18]. In a study surveying serum retinoids in 12 captive wild felid species, retinyl esters, predominantly stearate and palmitate, were detected in the serum of all species measured [27]. However, the proportion of VA present as esters ranged widely from 87% in the sand cat and 48% in the fishing cat to as low as 7% in cheetahs and cougars and 4% in servals.…”
Section: Vitamin Amentioning
confidence: 99%
“…Domestic cats consuming commercial diets seem to have very low to no circulating BC [18, 187]. However, Crissey et al [27] found relatively high concentrations of serum BC in 11 captive wild felid species kept in zoos. Dietary carotenoids were not quantified in this study, but regardless, wild felids seem to readily accumulate BC in blood.…”
Section: Species Differences In β-Carotene Metabolismmentioning
confidence: 99%
“…Serum vitamin A concentrations measured in four affected and two unaffected Sumatran tiger cubs were slightly below those reported in adult non-domesticated felid species (Ghebremeskel and Williams, 1988;Crissey et al, 2003;McCain et al, 2008). However, in these reports, sample sizes were small, and reference ranges for juvenile non-domesticated felids have not been established.…”
Section: Discussionmentioning
confidence: 63%
“…Serum calcium and inorganic phosphorus (mg/dl) were 10.97 and 3.63, respectively, from 1 female (Singh et al 1999b). Plasma protein and fibrinogen (g/dl) were 8.1 and 0.1, respectively (Jain 1986 (Crissey et al 2003).…”
Section: Form and Functionmentioning
confidence: 99%